KUALITAS PELAYANAN PENUMPANG PT. ASDP INDONESIA FERRY (PERSERO) CABANG KUPANG - Thomy Brandon Herson Welkis; Nursalam; Jim Briand Kolianan (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze and evaluate the quality of service delivery provided by PT. ASDP Indonesia Ferry (Persero) Kupang Branch at the Bolok Ferry Terminal, focusing on the five SERVQUAL dimensions: Tangible, Reliability, Responsiveness, Assurance, and Empathy. The findings indicate that the overall service quality has not yet reached an optimal level. The Tangible dimension reveals limitations in waiting-room facilities, particularly the insufficient availability of seating and ventilation equipment such as fans. The Reliability dimension is affected by inconsistencies in departure schedules, with frequent delays ranging from one to four hours. Meanwhile, although the Assurance dimension in terms of passenger safety is generally adequate, the practice of overcapacity loading on vessels poses potential risks to passenger comfort and safety. This study recommends improvements in time management, vessel capacity control, and physical facilities at the terminal in order to enhance overall service quality. The research employs a qualitative approach, with data collected through interviews, observations, and documentation.